2018
DOI: 10.1016/j.drugalcdep.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

AUDIT and AUDIT-C as screening instruments for alcohol problem use in adolescents

Abstract: Our results for the cut-off scores for the early detection of alcohol problem use in adolescents are ≥5 for AUDIT, and ≥3 for AUDIT-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 62 publications
1
67
0
2
Order By: Relevance
“…This applied to 61.9% of our sample. A dichotomous variable indicating problematic alcohol use, was computed based on a cut-off score of 5 or above on the total AUDIT score (Liskola et al 2018). This applied for 18.7% of our sample, with the highest observed AUDIT score being 24.…”
Section: Problematic Alcohol Usementioning
confidence: 99%
“…This applied to 61.9% of our sample. A dichotomous variable indicating problematic alcohol use, was computed based on a cut-off score of 5 or above on the total AUDIT score (Liskola et al 2018). This applied for 18.7% of our sample, with the highest observed AUDIT score being 24.…”
Section: Problematic Alcohol Usementioning
confidence: 99%
“…In addition, adolescents completed AUDIT (Reinert & Allen, 2002), which is a 10-item questionnaire measuring alcohol use and/or alcohol-related problems. The AUDIT has been reported to have acceptable psychometric properties when used with adolescents (Liskola et al, 2018;Santis et al, 2009).…”
Section: Screening Diagnostic and Outcome Measuresmentioning
confidence: 99%
“…), and therefore, it was decided not to complicate it further with some new questions to accurately calculate the binge drinking behavior (as stated in Section 2.4 ). Instead, it was decided to also use the AUDIT as a tool to characterize heavy alcohol consumers and binge drinkers, because some studies have demonstrated this possibility [ 7 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%